Sensor fotoeletroquímico para detecção de naproxeno em esgoto utilizando nanocomposto de vanadato de bismuto/óxido de cobre - Badaró, Carolina do Carmo (Universidade Federal de São Carlos, 2024)
Emerging pollutants are chemicals increasingly detected in the environment, often lacking analysis protocols and concentration limits regulated by governmental agencies. Pharmaceuticals are notable among these pollutants, found in sewage, surface water, groundwater, and even treated drinking water, often at very low concentrations but with potential environmental and public health impacts. Sewage treatment plants, though designed to remove various pollutants, may not effectively eliminate these emerging pollutants due to their persistence against conventional treatment processes. This study focuses on detecting naproxen in sewage using a photoelectrochemical sensor developed from the semiconductor material BiVO4/CuO. Morphological, structural, electronic, and electrochemical characterizations were conducted using X-ray diffraction, scanning electron microscopy, diffuse reflectance spectroscopy, and cyclic voltammetry. The sensor exhibited an analytical signal during photocurrent generation simultaneously with naproxen oxidation on the working electrode. Sensor responses were proportional to increased naproxen concentrations in the linear range of 0,02 μmolL-1 to 0,48 μmolL-1, with R2 = 0,997 and a detection limit of 4,90 nmolL-1. Naproxen detection in sewage samples was successfully achieved, with recovery percentages above 95%
Photoelectrochemical sensor for detection of naproxen em sewage using a bismuth vanatade/copper oxide nanocomposite
Keywords: Naproxeno; Sensor fotoeletroquímico; Análise ambiental; Vanadato de bismuto; Naproxen; Photoelectrochemical sensor; Environmental analysis; Bismuth vanadate; CIENCIAS EXATAS E DA TERRA::QUIMICA